Rotaxane and catenane host structures for sensing charged guest species. - Langton, M; Beer, P (2014)
CONSPECTUS: The promise of mechanically interlocked architectures, such as rotaxanes and catenanes, as prototypical molecular switches and shuttles for nanotechnological applications, has stimulated an ever increasing interest in their synthesis and function. The elaborate host cavities of interlocked structures, however, can also offer a novel approach toward molecular recognition: this Account describes the use of rotaxane and catenane host systems for binding charged guest species, and for providing sensing capability through an integrated optical or electrochemical reporter group. Particular attention is drawn to the exploitation of the unusual dynamic properties of interlocked molecules, such as guest-induced shuttling or conformational switching, as a sophisticated means of achieving a selective and functional sensor response. We initially survey interlocked host systems capable of sensing cationic guests, before focusing on our accomplishments in synthesizing rotaxanes and catenanes designed for the more challenging task of selective anion sensing. In our group, we have developed the use of discrete anionic templation to prepare mechanically interlocked structures for anion recognition applications. Removal of the anion template reveals an interlocked host system, possessing a unique three-dimensional geometrically restrained binding cavity formed between the interlocked components, which exhibits impressive selectivity toward complementary anionic guest species. By incorporating reporter groups within such systems, we have developed both electrochemical and optical anion sensors which can achieve highly selective sensing of anionic guests. Transition metals, lanthanides, and organic fluorophores integrated within the mechanically bonded structural framework of the receptor are perturbed by the binding of the guest, with a concomitant change in the emission profile. We have also exploited the unique dynamics of interlocked hosts by demonstrating that an anion-induced conformational change can be used as a means of signal transduction. Electrochemical sensing has been realized by integration of the redox-active ferrocene functionality within a range of rotaxane and catenanes; binding of an anion perturbs the metallocene, leading to a cathodic shift in the ferrocene/ferrocenium redox couple. In order to obtain practical sensors for target charged guest species, confinement of receptors at a surface is necessary in order to develop robust, reuseable devices. Surface confinement also offers advantages over solution based receptors, including amplification of signal, enhanced guest binding thermodynamics and the negation of solubility problems. We have fabricated anion-templated rotaxanes and catenanes on gold electrode surfaces and demonstrated that the resulting mechanically bonded self-assembled monolayers are electrochemically responsive to the binding of anions, a crucial first step toward the advancement of sophisticated, highly selective, anion sensory devices. Rotaxane and catenane host molecules may be engineered to offer a superior level of molecular recognition, and the incorporation of optical or electrochemical reporter groups within these interlocked frameworks can allow for guest sensing. Advances in synthetic templation strategies has facilitated the synthesis of interlocked architectures and widened their interest as prototype molecular machines. However, their unique host-guest properties are only now beginning to be exploited as a sophisticated approach to chemical sensing. The development of functional host-guest sensory systems such as these is of great interest to the interdisciplinary field of supramolecular chemistry.